The critical mutagenic translesion DNA polymerase Rev1 is highly expressed during G(2)/M phase rather than S phase - Waters, Lauren S; Walker, Graham C (Proceedings of the National Academy of Sciences - PNAS, 2006)
The Rev1 protein lies at the root of mutagenesis in eukaryotes. Together with DNA polymerase zeta (Rev3/7), Rev1 function is required for the active introduction of the majority of mutations into the genomes of eukaryotes from yeast to humans. Rev1 and polymerase zeta are error-prone translesion DNA polymerases, but Rev1's DNA polymerase catalytic activity is not essential for mutagenesis. Rather, Rev1 is thought to contribute to mutagenesis principally by engaging in crucial protein-protein interactions that regulate the access of translesion DNA polymerases to the primer terminus. This inference is based on the requirement of the N-terminal BRCT (BRCA1 C-terminal) domain of Saccharomyces cerevisiae Rev1 for mutagenesis and the interaction of the C-terminal region of mammalian Rev1 with several other translesion DNA polymerases. Here, we report that S. cerevisiae Rev1 is subject to pronounced cell cycle control in which the levels of Rev1 protein are approximately 50-fold higher in G(2) and throughout mitosis than during G(1) and much of S phase. Differential survival of a rev1Delta strain after UV irradiation at various points in the cell cycle indicates that this unanticipated regulation is physiologically relevant. This unexpected finding has important implications for the regulation of mutagenesis and challenges current models of error-prone lesion bypass as a process involving polymerase switching that operates mainly during S phase to rescue stalled replication forks.